2021
DOI: 10.1080/1331677x.2021.1962383
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the role of environmental taxes and regulations for renewable energy consumption: evidence from developed economies

Abstract: The current study aims to explore the role of environmental taxes and regulations for the renewable energy consumption, focusing on reporting policy suggestions to overcome climate change issues and achieve environmental sustainability. The main objective of this paper is to examine the relation between renewable energy, environmental taxes, environmental technologies, and environmental regulations in 29 OECD countries during 1996-2018. More precisely, we inspect the impact of the environmental regulations and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(31 citation statements)
references
References 97 publications
3
28
0
Order By: Relevance
“…Also, a study by Frankel and Romer (1999) confirmed that financial liberalization may drive FDI inflows, which, in turn, can hasten quick growth and, thus, harm environmental quality and increase carbon emissions. Also, renewable energy is the most efficient way to protect environmental quality (Bhattacharya et al, 2016;Sharif et al, 2019;Bashir et al, 2020;Bashir et al, 2021;Doğan et al, 2021;Fatima et al, 2021b;Shahzad et al, 2021a;Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Also, a study by Frankel and Romer (1999) confirmed that financial liberalization may drive FDI inflows, which, in turn, can hasten quick growth and, thus, harm environmental quality and increase carbon emissions. Also, renewable energy is the most efficient way to protect environmental quality (Bhattacharya et al, 2016;Sharif et al, 2019;Bashir et al, 2020;Bashir et al, 2021;Doğan et al, 2021;Fatima et al, 2021b;Shahzad et al, 2021a;Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Using data from German firms in 2009 ( 46 ) confirmed that the robust Porter Hypothesis was not always legal. According to Bashir et al ( 47 ), 28 subdivisions of China's manufacturing were categorized into efficiency-based groups. From 2003 to 2013, environmental regulations were ineffective in promoting ecological efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, citizens can raise their environmental awareness and become more involved in ecological monitoring. The government should swiftly enforce the law in response to citizen reports of environmental violations ( 47 ).…”
Section: Conclusion and Policy Recommendationsmentioning
confidence: 99%
“…Panel data from ( 36 ) showed that rising healthcare costs are linked to carbon emissions, harming residents' health. They also found that carbon emissions are harmful to the health of residents ( 37 ) utilized quasi-natural experiments and demonstrated that the continuous discharge of greenhouse gases is to blame for the rising infant mortality rate that has been observed in the United States. Researchers in Malaysia ( 38 ), Pakistan ( 39 ), and other countries in Sub-Saharan Africa found a link between carbon emissions and medical spending that was statistically significant ( 40 , 41 ).…”
Section: Literature Reviewmentioning
confidence: 99%